Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1177/1012690205052169
|View full text |Cite
|
Sign up to set email alerts
|

‘Bend It Like Patel’

Abstract: This article focuses on the experiences of Black women and one Indian Hindu woman in football in England. The discussions draw on survey and interview research to theorize gender, ‘race’ and ethnicity. The research represents a questionnaire survey of women’s teams and 14 semi-structured in-depth interviews; seven with players and seven with ‘officials’. The survey provides data on players, coaches and managers at women’s football clubs registered with the Football Association (FA) in the North of England. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(16 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…Sexuality has been focus for debate in women's football especially (Cahn, 1994;Caudwell, 1999Caudwell, , 2004Cox & Thompson, 2000). Race and ethnicity have been subject to some scrutiny (Ahmad, 2011;Ratna, 2013Ratna, , 2011Scraton, Caudwell, & Holland, 2005), but there is more theoretical work to be done here. Nevertheless, the composition of the sample was a mixture of white single women of various socio-economic backgrounds, and although participants did not talk comprehensively about sexuality, many were in heterosexual and couple relationships.…”
Section: Methodsmentioning
confidence: 98%
“…Sexuality has been focus for debate in women's football especially (Cahn, 1994;Caudwell, 1999Caudwell, , 2004Cox & Thompson, 2000). Race and ethnicity have been subject to some scrutiny (Ahmad, 2011;Ratna, 2013Ratna, , 2011Scraton, Caudwell, & Holland, 2005), but there is more theoretical work to be done here. Nevertheless, the composition of the sample was a mixture of white single women of various socio-economic backgrounds, and although participants did not talk comprehensively about sexuality, many were in heterosexual and couple relationships.…”
Section: Methodsmentioning
confidence: 98%
“…The failure to name whiteness has been noted by Scraton et al (2005) who state that White research participants are rarely defined in relation to their 'race' and ethnicity and the knowledge produced from their experiences is often used to theorise a universal experience, particularly for women (Bruening, 2005;Collins, 1986;Harris, 1990;hooks, 2015;Mirza, 2009Mirza, , 1997. The sample of coaching and equality staff who contributed to this article were all 'White', and were predominantly women.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we explore the opinions, attitudes and ideologies of stakeholders regarding 'race', ethnicity, racial equality, diversity, and whiteness in relation to sports coaching. Contrary to the popular belief that sport is a platform for equality and diversity, research reaffirms that sport coaching remains an arena in which interconnecting disparities of 'race', ethnicity, gender (as well as other social categories) create structured power relations that serve to reinforce patterns of inclusion / exclusion (Armstrong, 2007;King, 2001;Long, Hylton, Spracklen, Ratna, & Bailey, 2009;Scraton, Caudwell, & Holland, 2005;Sporting Equals, 2011;Sports People's Think Tank, 2014). Yet, the concepts of 'sport for all', equality of opportunity and inclusion have not been subject to rigorous analysis in sport or sport coaching research (Author B, 2012), with the exception of a few reports (Norman, North, Hylton, Flintoff, & Rankin, 2014;Sporting Equals, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, a statistic that is not often measured in such surveys, is the number of ethnic minority girls and young women playing the game. Scraton,Caudwell,and Holland,2 in their research about the footballing experiences of 'black' and British Asian 3 women, found that a number of them were known to be playing the game in England. Additionally, in my doctoral research, 4 I found more than 70 British Asian females playing at different levels of the Women's Football Pyramid.…”
Section: Introduction: 'Asian Girls Don't Play Football … Do They?'mentioning
confidence: 97%